Gender Equity In Hadith Literature: An Analysis Of The Contemporary Hadith Curriculum Of Madrasah Aliyah In Indonesia - Arifin, T. (Universiti Sains Islam Malaysia, 2024)
This paper stimulated by the fact that Muslim women participation in education in Indonesia is still lower than in neighbouring countries. This condition has been influenced by the weak support of Hadith Curriculum of Madrasah Aliyah toward gender equity. This condition has been miss understood by some scholars that Hadith does not support gender equity. The aims of this paper are to give a clear picture of gender equity in Hadith literature and analyse the content of Hadith Curriculum of Madrasah Aliyah in Indonesia in relation to gender equity support. Data were gained through Hadith literature and Hadith Curriculum of Madrasah Aliyah Year 2013. This study revealed that Hadith strongly support gender equity in all spects of life achieved as in economic, social, and political aspects. In addition, Hadith Curriculum of Madrasah Aliyah does not strongly support the emergence of strong and positive thinking toward gender equity among the students of Madrasah Aliyah who most of them then becoming religious leaders in Indonesian society. The implication of this finding requires us to make changes in the content structure of the Curriculum of Hadith for Madrasah Aliyah in Indonesia.